Teaching & learning in a South African school of social work - Moir, Jeni (My University, 2014)
This research explored social work education within a social development welfare paradigm in post-apartheid South Africa. The overall objective was to establish the suitability of an adult education orientation to the professional preparation of developmental social workers fo r practice in the South African context. The research was conducted among s ta ff and senior students of the School of Social Work at the University of the Witwatersrand during 1998. The enquiry is located within a post-positivist paradigm. The qualitative research was a reflexive process involving a critical review o f literature and exploration of the experiences of participants through written and verbal means as well as observation. The research established that an adult education approach was indeed appropriate fo r the professional education of developmental social workers. The implementation of adult education methodology was advocated in conjunction with a holistic realignment of the curriculum and sensitive engagement of role-players in an alternative style of teaching and learning.